Analysis of the Influence of Nurse Empathy and Burnout on Patient-Oriented Service Behavior (PSOB) at the Medan City Clinic - Dian Mawarni (Yayasan Multidimensi Kreatif, 2025)
This study aims to analyze the influence of nurse empathy and burnout on Patient-Oriented Service Behavior (POSB) in nurses in Medan City clinics. The research method used a quantitative approach by distributing questionnaires to 170 nurses. Multiple linear regression tests showed that empathy had a positive and significant effect on POSB with a coefficient of β = 0.487 and p = 0.000, while burnout had a significant negative effect with a coefficient of β = –0.325 and p = 0.000. Simultaneously, both variables exerted a significant influence on POSB (F = 53,821; p = 0,000), with a determination coefficient value of R² = 0.475 which means that 47.5% of POSB variations were explained by empathy and burnout. The results of the study confirm that increasing empathy and reducing burnout are important factors to strengthen patient-oriented service behavior. These findings provide implications for clinic management to improve the quality of services through empathy training and burnout management strategies.